Modulation of Risky Choices in Recently Abstinent Dependent Cocaine Users: A Transcranial Direct-Current Stimulation Study - Gorini, Alessandra; Lucchiari, Claudio; Russell-Edu, William; Pravettoni, Gabriella (Frontiers in Human Neuroscience, 2014)
Previous neurobiological and neuropsychological investigations have shown that risk-taking behaviors and addictions share many structural and functional aspects. In particular, both are characterised by an irresistible need to obtain immediate rewards as well as by specific alterations in brain circuits responsible for such behaviors. In this study, we used a transcranial direct-current stimulation (tDCS) over the dorsolateral prefrontal cortex (DLPFC) of two samples of subjects (18 dependent cocaine users and 18 control subjects) to investigate the effects of left and right cortical excitability on two risk tasks: the Balloon Analog Risk Task (BART) and the Game of Dice Task (GDT). All subjects randomly received a left anodal/right cathodal stimulation (LAn+), a right anodal/left cathodal stimulation (RAn+), and a sham (placebo) stimulation each run at least 48 hours apart. Participants were asked to perform the BART and the GDT immediately before and after each stimulation. Our results reveal that the activation of the DLPFC (left and right) results in a reduction of risky behaviors at the BART task both in controls subjects and cocaine dependent users. The effect of dTCS on GDT, instead, is more complex. Cocaine users increased safe behavior after right DLPFC anodal stimulation, while risk-taking behavior increased after left DLPFC anodal stimulation. Control subjects’ performance were only affected by the anodal stimulation of the right DLPFC, resulting in an increase of safe bets. These results support the hypothesis that excessive risk propensity in dependent cocaine users, might be due to a hypoactivation of the right DLPFC, as well as to an unbalance interhemispheres interaction. In conclusion, since risky decision-making seems to be, at least in part, responsible for maintenance and relapse of addiction, we argue that a neuromodulation-based approach could represent a valuable adjunct in the clinical treatment of addiction.